A preliminary investigation of gamification from the young consumer's perspective. Issue 3 (4th February 2021) - Hass, Danielle; Hass, Ashley; Joseph, Mathew
Abstract : Purpose: Over the past decade, gamification's popularity has broadened into many industries and has become embedded in consumers' lives. As privacy protection and how firms utilize users' data has been at the forefront of consumers' minds, practitioners and academics alike need to understand consumers' perceptions of the ethics of gamification. This paper aims to explore and provide preliminary evidence on young consumers' perceptions of gamification and the ethics involved in these strategies used by firms. Design/methodology/approach: The authors conducted two studies using a mixed-methods approach to gain a foundational understanding of young consumers' perceptions of gamification. In Study 1, interviews provided initial insights and helped inform an exploratory survey administered in Study 2 to 161 young consumers attending a university in the southwest region of the USA. Findings: The findings indicate that consumers have positive attitudes toward gamification tactics as long as the rewards are sufficient. Further, consumers do not find gamification as unethical as long as they have control over having the ability to opt-in. Originality/value: Previous research has examined gamification from several contexts including health care, education and the workplace. However, there is little research that focuses on gamification from the consumers' perspective, specifically the young consumer. As more firms are using gamification tactics such as on their mobile applications, it is critical to understand how young consumers perceive gamification and how that can impact the consumer-brand relationship. This research offers two studies as a first step in investigating young consumers' perceptions of gamification tactics firms use and offers several future directions.